ANALYSIS OF INDICATORS INFLUENCING DELAYS IN THE DEVELOPMENT OF ELECTRICAL POWER TRANSMISSION PROJECTS AT PLN UNIT INDUK PEMBANGUNAN JAWA BAGIAN TIMUR DAN BALI - Gesmulyadi; I Putu Artama Wiguna (RADJA PUBLIKA, 2026)
Delays in electricity transmission projects within PLN UIP JBTB have become a dominant issue. The majority of projects during the 2020–2024 period experienced delays, as reflected by milestone deviations, cost overruns, and time overruns, which disrupted electricity supply reliability and adversely affected the company’s corporate image. This study aims to analyze the indicators that form latent variables influencing project delays using an explanatory qualitative approach with the PLS-SEM method. Primary data were collected through questionnaires from 140 respondents selected via purposive sampling, comprising project owners, technical experts, and consultants. The results indicate that the elimination of the indicator related to community resistance to the project suggests that project delays are not driven by overt social opposition, but rather by weak communication quality and insufficient community engagement. In the licensing factor, all indicators demonstrate that project delays result from the cumulative effects of slow processing, administrative unpreparedness, and weak inter-agency coordination. Regarding the financial factor, project delays are more strongly influenced by the project financial system’s ability to maintain cash flow continuity and cost control than by perceptions of the financial impact of delayed payments. The human resources factor confirms that project delays are associated with an imbalance between workload and workforce capacity, competence, productivity, and motivation. Meanwhile, the logistics and supply chain factor indicates that unprepared procurement and material distribution systems are a significant source of project delays, even when construction activities are technically well planned.